Aloe-Emodin Induces Mitochondrial Dysfunction and Pyroptosis by Activation of the Caspase-9/3/Gasdermin E Axis in HeLa Cells - Li, Tonghui; Shi, Liuliu; Liu, Wenqiang; Hu, Xuhao; Hui, Yuanjian; Di, Maojun; Xue, Shen; Zheng, Yan; Yao, Mengjuan; Li, Chen; Meng, Kun (Frontiers in Pharmacology, 2022)
Aloe-emodin (1,8-dihydroxy-3-hydroxymethyl-anthraquinone), derived from some Chinese edible medicinal herbs, exerts a potential anticancer activity on various cancer cells, making it a drug candidate for cancer therapy. Yet, the role of aloe-emodin in pyroptosis, a new type of cell death, is uncharacterized. In this study, we explored the molecular mechanisms of aloe-emodin-triggered pyroptosis. Aloe-emodin inhibited proliferation and migration, and triggered caspase-dependent cell death of HeLa cells in a dose-dependent manner. Aloe-emodin caused mitochondrial dysfunction and induced pyroptosis by activating the caspase-9/3/GSDME axis. Transcriptional analysis showed extensive changes in gene expressions in cellular pathways, including MAPK, p53, and PI3K-Akt pathways when treated with aloe-emodin. This study not only identified a novel role of aloe-emodin in pyroptotic cell death, but also performed a systematical genome-wide analysis of cellular pathways responding to aloe-emodin, providing a theoretical basis for applying anthraquinone derivatives in the treatment of GSDME-expressing cancers.